Incidence, Risk Factors and Screening Evaluation of Retinopathy of Prematurity in High Birthweight Infants: A Large Cohort Study in Turkey - ŞAHİN, ÖZLEM; DERİCİOĞLU, VOLKAN (TAYLOR & FRANCIS INC, 2022)
Purpose: To report and evaluate the incidence and risk factors of retinopathy of prematurity (ROP) and to assess the sensitivity and specificity of Turkish national screening guideline (NSG) in heavier infants with a birth weight (BW) of >1500 g. Methods: The data of 1784 preterm infants with BW>1500 g, who were screened between 2009 and 2016 in a university hospital in Turkey, were analyzed retrospectively. The rates of any stage and severe (treatment-requiring) ROP incidence were investigated. The possible protective and risk factors were evaluated with univariate analyses and logistic regression analysis. Results: The rate of any stage ROP was 14.1% (n = 251). Severe ROP was observed in 11 infants (0.6%), and 2 of the infants (0.1%) had a gestational age (GA)>32 weeks, which fell outside of the NSG. In logistic regression analysis, BW, GA, O-2 therapy duration, and exchange transfusion were determined to be independent risk factors (respectively, p < .001, p < .001, P = .055, and P = .033). Furthermore, antenatal steroid therapy was determined to have a highly significant protective effect on ROP development (p < .001). The sensitivity of Turkish NSG in identifying severe ROP increased from 82% to 100% with the inclusion of risk factors in addition to GA and BW. Conclusion: This study shows the presence of severe ROP in mature and heavy infants in Turkey. The positive effect of antenatal steroid use and the negative impact of exchange transfusion have been demonstrated for ROP development in mature infants. Possible risk factors should be evaluated with GA and BW to avoid missing severe ROP.
Keywords: Retinopathy of prematurity; screening; sensitivity and specificity; heavy infants; mature infants; risk factors; antenatal steroid; exchange transfusion